The Swedes and their history. (1st July 2017) - Olofsson, Hans; Samuelsson, Johan; Stolare, Martin; Wendell, Joakim
Abstract : The aim of this article is to analyse adolescents' views of Swedish history. A small number of adults were also included in the study. The analysis shows that, regardless of the age of the informants, Sweden is portrayed as an exception from the world through its legacy of a long peace (in spite of a war-torn distant history) and through its enjoyment of progress, democracy and prosperity. We interpret this as a result of a history culture in which schools as well as other institutions produce a common, conflict-free history, which may be challenged in an emerging neonationalist era.